Analisis Faktor-Faktor yang Mempengaruhi Persepsi Mahasiswa dan Mahasiswi dalam Pemilihan Karir sebagai Akuntan Publik - Dendi Afrizal; Muhammad Mudzakkir (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
After completing their studies, accounting graduates are not limited to careers in the accounting field alone; they have a wide range of professional opportunities depending on the factors influencing their decisions. This study uses primary data, with the population consisting of undergraduate (S1) accounting students at Esa Unggul University. The sampling technique employed is nonprobability sampling using a snowball sampling approach. The results show that the simultaneous significance value is 0.000, which is less than 0.05. Partially, the salary variable has a significance value of 0.000, professional training 0.066, professional recognition 0.161, social values 0.734, and work environment 0.308. These findings indicate that, collectively, salary, professional training, professional recognition, social values, and work environment have a significant influence on accounting students’ perceptions in choosing a career as a public accountant. However, individually, only the salary or financial reward factor has a significant effect. Meanwhile, professional training, professional recognition, social values, and work environment do not have a significant influence on students’ decisions to pursue a career as a public accountant.